Öffentliche Haushalte 2008/2009: Spielräume für ein Konjunkturprogramm unzureichend genutzt - Achim Truger; Dieter Vesper (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2008)
Um zu verhindern, dass die deutsche Wirtschaft immer tiefer in den Abwärtssog der globalen Rezession gezogen wird, muss die Finanzpolitik entschlossen gegensteuern. Das von der Bundesregierung beschlossene Maßnahmenbündel ist hierfür völlig unzureichend. Durch ein hoch dosiertes und gezieltes Konjunkturprogramm von mindestens 25 Mrd. Euro im nächsten Jahr ließe sich dagegen die Stärke des Abschwungs vermindern und seine Dauer erheblich verkürzen. – – Public Spending 2008/2009Despite the strong cyclical downturn, German public budgets will be slightly in surplus this year (+ 0.2 per cent of GDP). Next year, however, the downturn will take effect and drive budgets back into a moderate deficit of 8 bn Euros (- 0.3 per cent of GDP). In order to prevent the German economy from sliding into a serious recession fiscal policy should take action. In this respect, the stimulus package planned by the German government is completely insufficient. It is as small as 0.3 per cent of GDP (cumulated over 2009 and 2010) and comprises mainly ineffective measures. Instead, the government should use a strong stimulus package of at least 25 bn Euros (1 per cent of GDP) to decrease both the extent and the duration of the economic crisis.
urn:nbn:de:101:1-20090317177
Keywords: 330; Finanzpolitik; Konjunkturpolitik; Öffentlicher Haushalt; Haushaltsdefizit; Finanzkrise; Wirtschaftskrise; Deutschland